2011
DOI: 10.1007/s00894-011-1221-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and nature of the intermolecular interactions in boron-bonded complexes with carbene as electron donor: an ab initio, SAPT and QTAIM study

Abstract: We report geometries, stabilization energies, symmetry adapted perturbation theory (SAPT) and quantum theory of atoms in molecules (QTAIM) analyses of a series of carbene-BX(3) complexes, where X = H, OH, NH(2), CH(3), CN, NC, F, Cl, and Br. The stabilization energies were calculated at HF, B3LYP, MP2, MP4 and CCSD(T)/aug-cc-pVDZ levels of theory using optimized geometries of all the complexes obtained from B3LYP/aug-cc-pVTZ. Quantitatively, all the complexes indicate the presence of B-C(carbene) interaction d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 53 publications
(53 reference statements)
2
10
0
Order By: Relevance
“…By applying the proposed decomposition scheme to a set of hydrogen and halogen bonding complexes, it was found that the decrease in H b toward negative values as the interaction strengthens is due mostly to the increase in the electrostatic contribution to the total interaction energy. In a recently published work on boron-based complexes with carbene as an electron donor [15], the authors found that the SAPT electrostatic energy correlates well with the H b value, therefore supporting our results.…”
Section: Introductionsupporting
confidence: 90%
“…By applying the proposed decomposition scheme to a set of hydrogen and halogen bonding complexes, it was found that the decrease in H b toward negative values as the interaction strengthens is due mostly to the increase in the electrostatic contribution to the total interaction energy. In a recently published work on boron-based complexes with carbene as an electron donor [15], the authors found that the SAPT electrostatic energy correlates well with the H b value, therefore supporting our results.…”
Section: Introductionsupporting
confidence: 90%
“…A nice correlation between the higher WBI values noted for the Ge-Ge bonds in 2 with an increase in the value of 1(r), which corresponds to the minimum electron density along a bond path, was noted (Supporting Information, Figure S6). [22] Moreover, a noticeable increase in covalent character of the Ge-Ge bonds, which is related to negative Laplacian 5 2 1(r) values in AIM, [24] was detected upon going from 1 (+ 0.004) to the branched species 2 (À0.006 to À0.035). The calculated linear isomer of 2, IPr- showing a preference for Ge-chain branching at higher Ge content; values in parentheses have been determined using a CH 2 Cl 2 solvation model.…”
Section: Methodsmentioning
confidence: 99%
“…e binding energy of the optimized complexes was also estimated at the DFT/B3LYP level of theory with polarization and diffuse functions added to minimize the basis set superposition error (BSSE). As each fragment uses the basis set of the others in the complex, smaller basis sets will result in decreased energy and an overestimation of the binding energy [36]. Generally, the interaction between the imidazol-2-ylidenes and the substituted boranes is made up of two factors: dative covalent bonding with σ-electron donation from the carbene carbon into sp 3 hybridized boron orbitals as well as intramolecular interactions between substituents on the borenium atom and the isopropyl groups on the N-atoms of the imidazol-2-ylidene ligand.…”
Section: Resultsmentioning
confidence: 99%